To speak about me is to speak about all of us: Memories and emotions among Afro-Argentine activists - Paola Monkevicius (Íconos, 2022)
This article analyzes the public discourses of Afro-Argentine women who occupy leadership positions within the Afro collective, observing intertwining between processes of remembrance, emotions, and political action. A qualitative approach based on face-to-face and virtual ethnographic practices was used. Differences are noted between the subalternized Afro-descendant memories of male leaders and those produced by women activists, who incorporate affective and biographical dimensions into the production of public narratives in spaces of dialogue between the Afro community and the state. The data were obtained from fieldwork conducted since 2011 in the area of the Autonomous City of Buenos Aires and its surroundings, both in associative and state spaces that were mainly used for commemorative purposes. For this, observation techniques were used with different degrees of participation, which made it possible to record practices and discourses. It is concluded that emotions fundamentally linked to collective pains shape the production of memories and support processes of Afro-female struggle, while they are communicated and shared, thus generating bonds of belonging and frameworks for political action, both within the collective and in relation to demands for rights before the national-state.